2008
DOI: 10.1016/j.rmed.2008.03.027
|View full text |Cite
|
Sign up to set email alerts
|

A prospective comparison of nursing home-acquired pneumonia with hospital-acquired pneumonia in non-intubated elderly

Abstract: There are no prospective comparison of the etiology and clinical outcome between hospital-acquired pneumonia (HAP) and nursing home-acquired pneumonia (NHAP) in non-intubated elderly. This study prospectively evaluated the etiology of HAP and NHAP in non-intubated elderly. A prospective cohort study was carried out in a rural region of Japan where the population over 65 years of age represents 30% of the population. A total of 108 patients were enrolled. There were 33 patients with HAP and 75 with NHAP. Etiolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
65
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 70 publications
(72 citation statements)
references
References 25 publications
6
65
0
Order By: Relevance
“…We found that patients with HCAP were older than those with CAP, results that support two studies from Japan [12,16]. Complications were also more frequently found in patients with HCAP.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…We found that patients with HCAP were older than those with CAP, results that support two studies from Japan [12,16]. Complications were also more frequently found in patients with HCAP.…”
Section: Discussionsupporting
confidence: 88%
“…Among these complications, central nerve diseases were more prevalent Seki et al, Page 15 15 in patients with HCAP, while chronic lung diseases and heart disease were more prevalent in patients with CAP. These characteristics were similar to the reports of Murayama et al [16], but much different from the results in the United States [4][5] suggesting a high frequency of aspiration pneumonia in elderly patients with old brain infarction in Japan.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…In agreement, an older study by Lim et al 18 and the CAPNETZ study 19 also reported that the most common pathogen in NHAP was S. pneumoniae (55%). In a study of similar design from Japan, Maruyama et al 20 identified C. pneumoniae, S. pneumoniae, S. aureus, and influenza virus as frequent causative agents of pneumonia in nonintubated institutionalized elderly persons. Interestingly, atypical pathogens accounted for 37% of all isolates.…”
Section: Etiologymentioning
confidence: 99%